Developing a Nurse-Delivered Frenulotomy Service. (January 2015) - Rose, Katie; Kasbekar, Anand V.; Flynn, Alison; De, Sujata
Objectives: Tongue tie (ankyloglossia) describes a short lingual frenulum that can lead to breastfeeding difficulties. It affects between 4% and 10% of infants and can be treated by frenulotomy. We developed a nurse-delivered frenulotomy service at a tertiary pediatric hospital and audited our results. Study Design: Observational study. Setting: Tertiary pediatric hospital. Subjects and Methods: An outpatient tongue tie clinic was set up by an ear, nose, and throat consultant. Tongue tie division was undertaken using a standard technique without the need for anesthesia or analgesia, as per National Institute for Health and Care Excellence guidelines. Subsequently, a senior nurse was trained to undertake the clinic independently and saw most referrals. Patient satisfaction data were collected via questionnaires. Results: Referrals to the service increased from 57 (2009) to 296 (2012). Outcome data from outpatient frenulotomy are discussed. Parent satisfaction measures were similar for both nurse- and doctor-delivered treatment. If all frenulotomies were undertaken in nurse-delivered clinics, a total of £3830 could have been saved in 2012, compared with the cost of doctor-delivered care. Conclusion: A nurse-delivered outpatient frenulotomy service is a safe and cost-effective method of delivering such care. We have demonstrated reduced costs and reduced waiting times without compromising patient satisfaction or the quality of care provided.